2018
DOI: 10.1097/ajp.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Sedation With Dexmedetomidine is Superior to Propofol for Elderly Patients Undergoing Hip Arthroplasty

Abstract: As a supplementary to peripheral nerve block, intraoperative sedation with dexmedetomidine could be associated with a lower incidence of POD, which may have benefits on reducing the incidence of early POCD and offering a better short-term recovery for elderly patients receiving hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 34 publications
2
52
0
2
Order By: Relevance
“…Two RCTs did not state study dates [ 39 , 40 ]. Sixteen RCTs dealt with surgical patients, nine of which were cardiac surgery RCTs [ 36 , 39 , 41 , 42 , 45 47 , 51 , 53 ] and seven non-cardiac surgery RCTs, meaning microvascular free flap surgery [ 34 ], joint replacement [ 49 ] or total hip arthroplasty [ 54 ], major abdominal surgery [ 52 ], major laparoscopic surgery [ 55 ], and elective non-cardiac surgery under general anesthesia [ 33 , 48 ]. The remaining nine RCTs consisted of six studies examining MV patients [ 32 , 38 , 40 , 43 , 44 , 50 ] two examining noninvasively ventilated patients [ 35 , 37 ] and one where dexmedetomidine was used for nightly sedation [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs did not state study dates [ 39 , 40 ]. Sixteen RCTs dealt with surgical patients, nine of which were cardiac surgery RCTs [ 36 , 39 , 41 , 42 , 45 47 , 51 , 53 ] and seven non-cardiac surgery RCTs, meaning microvascular free flap surgery [ 34 ], joint replacement [ 49 ] or total hip arthroplasty [ 54 ], major abdominal surgery [ 52 ], major laparoscopic surgery [ 55 ], and elective non-cardiac surgery under general anesthesia [ 33 , 48 ]. The remaining nine RCTs consisted of six studies examining MV patients [ 32 , 38 , 40 , 43 , 44 , 50 ] two examining noninvasively ventilated patients [ 35 , 37 ] and one where dexmedetomidine was used for nightly sedation [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a case report, it was reported that DEX was effective as a sedative and analgesic for a total hip replacement patient [31]. In a recent research, Mei et al reported that the intraoperative sedation of DEX was better than propofol in THA for elder patients [32]. In addition, the combined use of DEX and other block anesthetic methods have also been reported in several studies.…”
Section: Discussionmentioning
confidence: 97%
“…Intraoperative sedation during RA has the benefit of avoiding postural discomfort, preventing intraoperative recall, and reducing autonomic reflexes [17]. Recently, prophylactic low-dose DEX significantly decreases the occurrence of postoperative delirium after noncardiac surgery and hip arthroplasty [17,18]. Patients presenting with proximal femur fracture are usually elderly and therefore a significant proportion have coexistent disease and a high risk factor of postoperative delirium (POD).…”
Section: Discussionmentioning
confidence: 99%